1999
DOI: 10.1016/s0304-3959(98)00239-5
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and pregabalin, but not morphine and amitriptyline, block both static and dynamic components of mechanical allodynia induced by streptozocin in the rat

Abstract: A single injection of streptozocin (50 mg/kg, i.p.) led to the development of static and dynamic allodynia in the rat. The two responses were detected, respectively, by application of pressure using von Frey hairs or lightly stroking the hind paw with a cotton bud. Static allodynia was present in the majority of the animals within 10 days following streptozocin. In contrast, dynamic allodynia took almost twice as long to develop and was only present in approximately 60% of rats. Morphine (1-3 mg/kg, s.c.) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
159
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(180 citation statements)
references
References 44 publications
17
159
2
2
Order By: Relevance
“…Yet, administration of gabapentin into the hind paw failed to block both the static and dynamic allodynia induced by streptozocin in rats. 33 This discrepancy with our study is possibly due to the different animal models (streptozocin vs spinal nerve ligation) and the different types and doses of drugs (gabapentin 1-100 lg/animal vs pregabalin 10-50 mgÁkg -1 ). Pregabalin-related side effects include mild-to-moderate central nervous system disturbances, such as dizziness, somnolence and ataxia, dose-dependent peripheral edema, weight gain, 34,35 myoclonus, 36,37 a cortical negative form of myoclonus, 38 and exacerbation of heart failure.…”
Section: Discussioncontrasting
confidence: 82%
“…Yet, administration of gabapentin into the hind paw failed to block both the static and dynamic allodynia induced by streptozocin in rats. 33 This discrepancy with our study is possibly due to the different animal models (streptozocin vs spinal nerve ligation) and the different types and doses of drugs (gabapentin 1-100 lg/animal vs pregabalin 10-50 mgÁkg -1 ). Pregabalin-related side effects include mild-to-moderate central nervous system disturbances, such as dizziness, somnolence and ataxia, dose-dependent peripheral edema, weight gain, 34,35 myoclonus, 36,37 a cortical negative form of myoclonus, 38 and exacerbation of heart failure.…”
Section: Discussioncontrasting
confidence: 82%
“…Formalin-evoked hyperalgesia in diabetic rats shares some features with the allodynia present in diabetic animals. These features include prevention by insulin therapy [22] and alleviation by gabapentin [37,38] or a prosaposin-derived peptide [39], but they differ in responsiveness to aldose reductase inhibition [1,22]. In the present study we found that phase 2 of formalin-evoked hyperalgesia in diabetic rats was alleviated by systemic asimadoline and this was partially blocked by systemic or intrathecal nor-BNI, indicating KOR involvement in the mechanism of action of asimadoline.…”
Section: Discussionsupporting
confidence: 49%
“…Interestingly, vincristine-induced allodynia in Harlan rats is less sensitive to treatment with gabapentin ( Fig. 4E) than that in Holtzman rats to treatment with pregabalin (Nozaki-Taguchi et al, 2001), a similar but more potent antiallodynic drug (Field et al, 1999). It seems that the gabapentin insensitivity in our VIN rats is not due to inadequate dose of the drug because both drugs have similar binding affinities to the ␣ 2 ␦-1 subunit (Suman-Chauhan et al, 1993) and the difference in drug doses between our study (up to 300 mg/kg gabapentin i.p.)…”
Section: Discussionmentioning
confidence: 93%
“…Spinal administration of gabapentin, a novel anticonvulsant that binds to the ␣ 2 ␦ subunits of the voltage-gated calcium channels in vitro (Marais et al, 2001), suppresses allodynia in neuropathic pain models without general analgesic effects (Hwang and Yaksh, 1997;Abdi et al, 1998;Field et al, 1999). In addition, the potencies of gabapentinoids against neuropathic pain correlate with their sterospecificity and binding affinities at the ␣ 2 ␦ site (Suman-Chauhan et al, 1993;Dissanayake et al, 1997;Hwang and Yaksh, 1997).…”
mentioning
confidence: 99%